Effect of sewage water and plant growth regulators on growth and yield of Mung Bean (Vigna radiate L.) - Hassan, Muhammad Wajihul; Yasmeen, Azra; Idrees, Muhammad Aqib; Hussain, Kamil; Talib, Irfan; Jalani, Tehseen Ali; Noor Ul Ain; Ghafoor, Iqra; Khan, Mehboob; Masood, Muhammad; Abdul Aziz (Indus Journal of Bioscience Research, 2025)
The current scenario of water scarcity and the disposal problem of sewage water leads to its use in agriculture. Despite being rich of organic matter; sewage water may suppress crop growth and yield due to nutrient toxicity. In such case, growth regulators usage can ensure crop productivity under sewage water irrigations. In this study, the effect of exogenously applied growth regulators Moringa (Moringa oleifera L.) leaf extract (MLE) and Thiourea (TU) on mung bean plants irrigated with sewage water was evaluated. Field trials were conducted at Bahauddin Zakariya University, Multan, Pakistan, during the spring season of 2016 and 2017, using Randomized Complete Block Design (RCBD) with factorial arrangements and three replications. Treatments included different irrigation water sources (Tube well (TW) as a control, sewage water (SW) and mixed water (TW + SW)) in main plots and exogenously applied plant growth regulators (30 times diluted MLE; TU at rate of 1000 ppm; distilled Water (DW) as control) applied before and after flowering in sub-plots. Results revealed that interaction of mixed water irrigation with foliar application of MLE significantly enhances leaf chlorophyll ‘a’ and ‘b’ contents, antioxidant activity and improves plant growth characters like number of branches, leaves, plant height, and number of pods during both years. In comparison to control, MLE interaction with mixed water irrigation significantly improved the yield of mung by producing 45.6% and 4.9% more grain yield, 138% and 13.3% biological yield, and 60.2% and 60.3% heavier thousand grains weight during 2016 and 2017, respectively. MLE exogenous application on sewage water irrigated plants also produced significantly better yield followed by thiourea sprayed on sewage water irrigated plants. It was concluded that sewage water can only be used for crop production after water analysis, and for higher yields under semi-arid conditions, foliar application of MLE followed by TU can be recommended.